Kajian sosioperundangan perkahwinan merentasi sempadan di nusantara - Md Said, Muhamad Helmi; Md Hashim, Noraini; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Ahmad Fuzi, Fauziah Hani; Yaakob, Khairulshuhadah (Universiti Sultan Zainal Abidin, 2020)
Background and Purpose: Due to the increase in the number of cross-border marriage and limited research available in the area, the paper sets on discussing the application of the related laws and practices that surround cross border marriage among the Muslims in Malaysia. Methodology: This research used the socio-legal approach and qualitative method. The data had been obtained through interviews with 11 informants, consisting of officials of the religious office in Malaysia and in Southern Thailand, officials of the Malaysian Consulate in Songkhla, Thailand as well as couples who practised cross-border marriage. Apart from that, analysis document had been used to analyse statutes and reported cases. Findings: This research shows that the practice of cross-border marriage among Muslims couples in Malaysia is due to strict implementation of the law and their acceptance and openness in going for cross- border marriage. The lacuna of specific provisions relating to cross-border marriage in the law has led to global legal issues that require resolution using international instruments. Contributions: This article is hoped to pave the way for a more comprehensive study on the cross-border marriage which the findings will be useful to further improve the current legal provisions in Malaysia.